2019
DOI: 10.1093/eurpub/ckz106
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in home care recipients after a falls prevention intervention: a 6-month follow-up

Abstract: Background: Falls in older adults are an increasingly important public health concern due to the expanding older population and contribute considerably to the global burden of disease. Home care recipients have a high incidence of falls and a low level of health-related quality of life (HRQOL). In this understudied group of older adults, exercise interventions could prevent falls, promote HRQOL and enable healthy ageing in the longer term. Methods:The study is a single-blinded parallel-group randomised control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…However, their impact on competence should not be disregarded. In addition, the perception of competence is closely linked to patient outcomes [15,16]. This link between perceptions of competence and patient outcomes could be explained by the general emphasis on the problem-solving competence by the professionals themselves, as shown in earlier research [57].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…However, their impact on competence should not be disregarded. In addition, the perception of competence is closely linked to patient outcomes [15,16]. This link between perceptions of competence and patient outcomes could be explained by the general emphasis on the problem-solving competence by the professionals themselves, as shown in earlier research [57].…”
Section: Discussionmentioning
confidence: 84%
“…To answer the research question, we used a purposive sample, which are used when the opinion of experts in a particular field is the topic of interest [14]. The current study was conducted in six municipalities in Eastern Norway, where the participating PTs had earlier been involved in a randomised controlled trial evaluating a fall preventative exercise programme [15,16]. All informants had clinical experience in the area of fall prevention and working with older adults.…”
Section: Informants and Settingmentioning
confidence: 99%
“…A systematic review examining community-based exercise interventions found that these interventions are valuable for reducing the incidence of falls when these interventions focus on improving balance and include functional and resistance exercises [40]. A randomized controlled trial from Norway on exercise programs also found positive results with respect to improving physical health-related quality of life [41]. These findings demonstrate the value of exercise interventions for home care clients to reduce the incidence of accidental falls and improve patient safety in home care settings.…”
Section: Implications For Policies and Practices Pertaining To Home Carementioning
confidence: 99%
“…However, uptake and adherence to such interventions is often poor [11][12][13] . Home care is also an important arena to address falls prevention and QOL, but this vulnerable group of older adults is underrepresented in health research 14 . One recent study of a falls prevention exercise programme based on the Otago Exercise Programme (OEP) significantly improved physical function, Health Related Quality of Life (HRQOL) and balance in older adults receiving home care but was cost intensive 14 .…”
Section: Jfsf 11mentioning
confidence: 99%
“…Home care is also an important arena to address falls prevention and QOL, but this vulnerable group of older adults is underrepresented in health research 14 . One recent study of a falls prevention exercise programme based on the Otago Exercise Programme (OEP) significantly improved physical function, Health Related Quality of Life (HRQOL) and balance in older adults receiving home care but was cost intensive 14 . Integrating strength and balance activities into daily life activities has shown better adherence but there are less studies in those receiving care 15 .…”
Section: Jfsf 11mentioning
confidence: 99%